Building defect management: a case study at The Havre, Bukit Jalil / Muhamad Afiq Hakim Shamsul Anuar - Shamsul Anuar, Muhamad Afiq Hakim (Universiti Teknologi MARA, Perak, 2018)
To perform rational defect prevention, it is necessary to have knowledge about defects, their causes and associated costs. Defect is a very important factor to be taken seriously, therefore this report will discuss about defects management and how to solve it in a house unit. This report was conducted to investigate the High-rise building Unit defects for PHASE 2A, THE HAVRE BUKIT JALIL. The objective of this report is to identify the high-rise building unit defects by executing detailed inspections on all 15 units of houses at each floor. It will focus on identifying defects that clients did not aware of. To identify the method of rectification for the defects after it has been identified by using the right material and the appropriate time. This report will also look at the execution of rectifying the defects by choosing the right person to execute the works and thus by following these objectives it could minimise the amount of the defects that existed in the house unit in the future.